Multimedia over IP and wireless networks : compression, networking, and systems - Chou, Philip A.; Schaar, Mihaela van der (Elsevier/Academic Press, 2007)
This all-inclusive, expertly structured contributed volume will serve as an indispensable guide for professionals or researchers working in areas like networking, communications, data compression, multimedia processing, streaming architectures, and computer graphics. Beginning with a concise overview of the fundamental principles and challenges of multimedia communication and networking, this book then branches off organically to tackle compression and networking next before moving on to systems, wireless multimedia and more advanced topics. The Compression section advises on the best means and methodology to ensure multimedia signal (images, text, audio and data) integrity for transmissions on wireless and wired systems. The Networking section addresses channel protection and performance. In the Systems section the focus is on streaming media on demand, live broadcast and video and voice's role in real-time communication. Wireless multimedia transmission and Quality of Service issues are discussed in the Wireless Multimedia section. An Advanced Topics section concludes the book with an assortment of topics including Peer-to-Peer multimedia communication and multipath networks. * Up-to-date coverage of existing standards for multimedia networking * Synergistic tutorial approach reinforces knowledge gained in previous chapters * Balanced treatment of audio and video with coverage of end-to-end systems.